Protecting whales by distorting uncertainty: non-precautionary mismanagement? - Schweder, Tore (Fisheries Research, 2001)
Precautionary management is based on science, and is incompatible with large fluctuations in the management regime. Whaling is managed by the International Whaling Commission, and has seen large fluctuations. It is argued that both the period of intense Antarctic whaling and the current period of protectionism have been unduly prolonged by scientists expanding out of proportion the uncertainty surrounding management issues. In the 1950s, uncertainty concerning fin whale stock status and trend was consistently distorted from one quarter, and in the 1990s a minority in the Scientific Committee blocked consensus over the revised management procedure that had been successfully developed by the Committee. In both cases, the political consequence of expanded uncertainty in the science was lack of action resulting in a continuation of business as usual. Extending a period of heavy exploitation longer than the resource can sustain is mismanagement. Extending a period of extreme protectionism when the resource is known to scientists to sustain valuable exploitation is also mismanagement even from a conservationist point of view. This might, in fact, erode the role of science in management and thus prepare the ground for subsequent overexploitation. Distorting uncertainty by injecting controversy or otherwise expanding uncertainty has contributed to excessive fluctuations in management regimes and consequently in stock abundance. Detrimental fluctuations might continue, since science is side tracked and management now is based on sentiments that might fade.
Keywords: Den internasjonale hvalfangstkommisjonen; Sørishavet; fiskeri; hvalfangst; marine økosystemer

Åpning av Foyn-seminaret 23.januar 1995 - Olsen, Jan Henry T (Vestfoldminne, 1995)
Publisher: Vestfoldmuseene
Keywords: Den internasjonale hvalfangstkommisjonen; Norge; Svend Foyn; Sørishavet; historie; hvalfangere; hvalfangst; hvalfangstkvotene; pelagisk

Hvalfangsforhandlingene i historisk og prinsipielt perspektiv: økonomi, biologi, politikk - Midgaard, Knut (Forskningspolitiske spørsmål i norsk biologi : en seminarrapport = Policy issues in Norwegian biological research : report from a seminar, 1974)
I. Vi skal i det følgende beskjeftige oss med forhandlingene om regulering av den pelagiske hvalfangst i Antarktis med sikte på å belyse to emner: 1) betingelsene for at biologers premisser skal slå igjennom i en politisk prosess som gjelder utnyttelsen av levende ressurser, 2) rollekonflikter som kan oppstå for biologer som går inn i en slik prosess. Jeg vil først gi en historikk, og så gå nærmere inn på de to emnene.
https://hdl.handle.net/11250/2486546
Keywords: Den internasjonale hvalfangstkommisjonen; Norge; Sørishavet; hvalfangstkonvensjonen; hvalfangstkvoter; internasjonal politikk; pelagisk hvalfangst